Eritrosit dan Hemoglobin pada Kelelawar Gua di Kawasan Karst Gombong, Kebumen,Jawa Tengah - Wijayanti, Fahma; Solihin, Dedy Duryadi; Alikodra, Hadi Sukadi; Maryanto, Ibnu (Perhimpunan Biologi Indonesia, 2011)
ABSTRACTErythrocyt and Haemoglobin on Cave Bat at Gombong Karst Area, Kebumen Regency, CentralJawa. The purpose of this study was observe physiological adaptation of the cave batsconducted from September 2009 to March 2010 in twelve caves within the karst of Gombong,Kebumen Regency, Central Java. In each caves where the bats roosting, temperature, alsohumidity, oxygen percentage in the air, and ammonia content were measured. Three individualsamples were caught from every bat roost during the day when the bats were staying in theirroosts. Then the amount of erythrocyte was counted by hemocytometer and hemoglobincontent was measured using Sahlis method. The data were analyzed using RDA and multipleregressions. It was concluded that humidity, temperature, oxygen and ammonia correlatedsignificantly with erythrocyte and hemoglobin content. The amount of erythrocyte increasedby increasing humvel.Keywords: Bat, cave, erythrocyte, haemoglobin.